Monographie der palaearktischen Lonchaeidae (Diptera). - Morge, Günter (Beiträge zur Entomologie = Contributions to Entomology, 1962)
Nomenklatorische Handlungen adriatica (Becker, 1895) (Earomyia), Lectotype described as Lonchaea adriatica albifacies (Czerny, 1934) (Earomyia), Lectotypus described as Spermatolonchaea albifacies caudicola Morge, 1962 (Earomyia), spec. n. grusia Morge, 1962 (Earomyia), spec. n. impossibile Morge, 1962 (Earomyia), spec. n. frontata Becker, 1895 (Lonchaea), Lectotype now synonym of Earomyia lonchaeoides Zetterstedt, 1848 inaequalis Loew, 1873 (Lonchaea), Lectotype now synonym of Earomyia nigra (Meigen, 1826) nigroviolacea Frey, 1931 (Lonchaea), syn. n. of Earomyia crystallophila (Becker, 1895) helvetia Czerny, 1934 (Spermatolonchaea), Lectotype; syn. n. of Earomyia crystallophila (Becker, 1895)